Índice de aptidão de áreas para projetos de renovação urbana: estudos de caso das cidades de Cali na Colômbia e São Paulo no Brasil - Perea Álvarez, Randy (Universidade Federal de São Carlos, 2023)
The majority of traditional centers in large cities in Latin America undergo processes of physical deterioration and population decline, demanding urban planning alternatives to address these issues. One possibility to enhance, valorize, improve, and integrate established areas within the city is through urban renewal, driven by a change in patterns that aim to stimulate mixed-use development and avoid urban expansion. This research proposes a method that relates qualitative and quantitative urban variables within analysis categories specific to urban renewal, such as land management, building capacity and urban conditions. The objective is to develop an area aptitude index for urban renewal projects (IAPRU) in the city centers of Cali, Colombia, and São Paulo, Brazil, during the year 2022. The results of the prioritized areas, as determined by the IAPRU, are presented through tables and thematic cartography produced using geographic information systems (GIS) tools.
Index of areas aptitude for urban renewal projects: case studies from the cities of Cali in Colombia and São Paulo in Brazil
Keywords: Renovação urbana; Índice; Gestão do solo; Edificabilidade; Condições urbanísticas; SIG; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::TECNOLOGIA DE ARQUITETURA E URBANISMO; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA